The Impact of Meeting Donor Management Goals on the Development of Delayed Graft Function in Kidney Transplant Recipients. Issue 4 (13th February 2013) - Malinoski, D. J.; Patel, M. S.; Ahmed, O.; Daly, M. C.; Mooney, S.; Graybill, C. O.; Foster, C. E.; Salim, A.; ,
Abstract : Many organ procurement organizations (OPOs) utilize preset critical care endpoints as donor management goals (DMGs) in order to standardize care and improve outcomes. The objective of this study was to determine the impact of meeting DMGs on delayed graft function (DGF) in renal transplant recipients. All eight OPOs of the United Network for Organ Sharing Region 5 prospectively implemented nine DMGs in every donor after neurologic determination of death (DNDD). "DMGs met" was defined a priori as achieving any seven of the nine DMGs and this was recorded at the time of consent for donation to reflect donor hospital ICU management, 12–18 h later, and prior to organ recovery. Multivariable analyses were performed to identify independent predictors of DGF (dialysis in the first week after transplantation) with a p < 0.05. A total of 722 transplanted kidneys from 492 DNDDs were included. A total of 28% developed DGF. DMGs were met at consent in 14%, 12–18 h in 32% and prior to recovery in 38%. DGF was less common when DMGs were met at consent (17% vs. 30%, p = 0.007). Independent predictors of DGF were age, Cr and cold ischemia time, while meeting DMGs at consent was significantly protective. The management of potential organ donors prior to consent affects outcomes and should remain a priority in the intensive care unit. Abstract : The authors report that meeting a bundle of preset critical care endpoints, or donor management goals, independently predicts a lower delayed graft function rate.